Factors Affecting Teacher Productivity in Banten Province - Dzikri, Ahlu; Fulaisum Firdaus, M (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
In this study, there are limitations that are carried out, namely the researcher only researches in private and public vocational schools throughout the city of Cilegon. Quantitative research uses a correlational approach. The population of this study is all private and public vocational school teachers in Cilegon City as many as 600 people with 27 schools. The 10% sample consisted of 600 teachers and the total used was 86 teachers. Proportional random sampling is used as a sampling technique. Data collection is carried out by a survey method using research instruments developed by researchers by following the dimensions and indicators of experts. The questionnaire used a Likert scale with five categories of alternative answers ranging from strongly agreeing to agreeing, Neutral, disagreeing, and strongly disagreeing. Data analysis was carried out using Smart-PLS 3.2.7. The findings of this study reveal 1) There is a direct relationship between motivation and creativity, with a coefficient of R2 of 0.241; 2) Between motivation and productivity, there is a significant direct influence, with R2 of 0.083, t-statistic of 2.709 > 1.96, p-value of 0.007 < 0.05; 3) There is a significant direct relationship between career development and Creativity, with an R2 of 0.625; 4) career development has a significant direct effect on productivity, with an R2 coefficient of 0.750, t-statistics of 10.463 >1.96, and p-value of 0.000 < 0.05; 5) creativity has a significant direct influence on teacher productivity, with an R2 coefficient of 0.676, t-statistics of 11.619 >1.96, and p-value of 0.000 < 0.05; 6) Through Creativity, there was a significant indirect influence of Motivation on Teacher Productivity, with an R2 coefficient of 0.111, t-statistic of 2.952 >1.96, and p-value of 0.003 < 0.05; 7) In the seventh hypothesis, from the results of the hypothesis test, the R2 coefficient is 0.061, the t-statistic is 3.042 >1.96, and the p-value is 0.002 < 0.05, so that there is a significant indirect influence between Career Development and productivity through Creativity at Cilegon City Vocational School.